2022
DOI: 10.3390/children9060885
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Neglect Awareness among Medical Students

Abstract: Physical, emotional, and sexual abuse and various forms of neglect of children have been encountered more frequently by healthcare providers, particularly physicians. However, mismanagement of child abuse and neglect (CAN) due to a lack of awareness of it can lead to substantial and serious consequences. This study primarily aimed to evaluate the awareness of CAN among medical students and compare it between preclinical and clinical males and females in Imam Abdulrahman Bin Faisal University in Dammam, Saudi A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 23 publications
(36 reference statements)
9
14
1
1
Order By: Relevance
“…According to our findings, the education provided by the medical and nursing curriculum was considered insufficient by the students themselves because only 19.7% of the participants reported having a chapter that covered CAN in their curriculum, while 27.3% reported that a professor took the initiative to discuss CAN. Similar findings can be seen in studies in China, the USA, and Saudi Arabia [ 15 , 16 ]. It is of interest to note that students in clinical years of medical and nursing studies reported a lack of confidence in handling a suspected case of CAN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our findings, the education provided by the medical and nursing curriculum was considered insufficient by the students themselves because only 19.7% of the participants reported having a chapter that covered CAN in their curriculum, while 27.3% reported that a professor took the initiative to discuss CAN. Similar findings can be seen in studies in China, the USA, and Saudi Arabia [ 15 , 16 ]. It is of interest to note that students in clinical years of medical and nursing studies reported a lack of confidence in handling a suspected case of CAN.…”
Section: Discussionsupporting
confidence: 90%
“…This intention was not correlated with the faculty to which the students belonged, their gender, or the year of their studies. A similar need was shown in other studies as well [ 16 , 17 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, most of the students in our study were reasonably aware of CAN, with the majority acknowledging its existence in Saudi Arabia. In addition, most students agreed that CAN would affect the patient's well-being in the future, which aligns with the study findings of Al-Qahtani et al who studied the knowledge levels and educational experiences among dental graduates in Saudi Arabia regarding child abuse and neglect [22].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the sources of information about child abuse and neglect, social media emerged as the most accessed source among dental students, with 85.0% reporting it as a source of information, which agrees with the Al-Qahtani et al study, where the majority of participants believed that social media played a significant role in disseminating information about CAN [22]. Interestingly, we found that the dental college was reported as the least utilized source of information about child abuse and neglect, with only 50% of students perceiving it as a source.…”
Section: Discussionsupporting
confidence: 84%
“…Some studies were conducted to assess the awareness of parents, teachers, health professionals, and the public about child abuse [11][12][13]. However, most of these studies focused on health professionals and teachers who are assumed to have more knowledge due to their training.…”
Section: Introductionmentioning
confidence: 99%